Touching the Void: Exploring Virtual Objects through a Vibrotactile Glove - Giannopoulos, Elias; Pomes, Ausias; Slater, Mel (International Journal of Virtual Reality, 2012)
This paper describes a simple low-cost approach to adding an element of haptic interaction within a virtual environment. Using off-the-shelf hardware and software we describe a simple setup that can be used to explore physically virtual objects in space. This setup comprises of a prototype glove with a number of vibrating actuators to provide the haptic feedback, a Kinect camera for the tracking of the user’s hand and a virtual reality development environment. As proof of concept and to test the efficiency of the system as well as its potential applications, we developed a simple application where we created 4 different shapes within a virtual environment in order to try to explore them and guess their shape through touch alone.